GRADUATE STUDENTS’ SYNTACTICAL ERRORS IN WRITING THESIS - Hanna Meilinda Rodearni Sinaga; Lince Sihombing (State University of Medan, 2014)
ABSTRACT This study deals with the graduate students’ syntactical errors in writing thesis. This thesis describes the syntactical errors made by the graduate students of English Department and Applied Linguistics of the State University of Medan in writing thesis. One of the purposes of writing thesis is to know the types of syntacticalerror and the dominant types. This study uses a qualitative design in which the data are taken from the sentences of thesis. The data are collected and described using surface strategy taxonomy proposed by Dulay, Burt, and Krashen. Then, the errors found are classified into syntactical errors based on Politzer and Romirez’ model as a guideline. The researcher applies randomly technique to get a representative sample, there are 6 theses as the sample. The findings of analysis show that the totals of syntactical errors are 387 sentences. The analysis found that there are four types of syntactical errors which used; they are Omision156, Addition 46, Misformation 114 and Misordering 19. The most dominant type of syntactical errors made in graduate students’ thesis is omission. Keywords:Syntactical Errors, Thesis.